Land-use Decisions in Complex Commons: Engaging Multiple Stakeholders through Foresight and Scenario Building in Indonesia - Shantiko, B.; Liswanti, N.; Bourgeois, R.; Laumonier, Y. (Springer, 2021)
In the midst of global change uncertainties, Indonesian spatial planning authorities are developing 20-year strategies. However, the lack of collaborative engagement of stakeholders and unclear methodology around using futures studies in addressing land management undermine such plans and affect environmental governance. A crucial question is how to link a future-oriented process with governance transformation processes, particularly related to land-use planning and management. To address this issue, we used a co-elaborative scenario-building approach, referred to as participatory prospective analysis (PPA), to facilitate the creation of local multistakeholder platforms considering future-oriented perspectives. The PPA design combines equally the knowledge of local communities, technical experts and decision-makers, and was applied in a series of sequential multistakeholder workshops in two regencies in Indonesia, followed by public consultations on the main results. In both regencies, participants agreed on a common topic related to spatial planning in their jurisdiction to be explored with a 20-year time horizon. They reached consensus on relevant variables, analyzed their dependence/influence, and developed several plausible yet contrasting scenarios for land management and road maps with guidelines for the implementation of desired outcomes. The PPA approach stimulated stakeholder engagement and ensured that more local voices were not only heard but also duly included in the process. It allowed participants to consider strategies that would otherwise have been less readily accepted by their respective organizations. It showed that it is possible to improve existing spatial planning processes in Indonesia by integrating tools for a more inclusive and long-term future-oriented collaborative approach.